Mental health disparities in young adults with arrest history: a survey-based, cross-sectional analysis - Onur Baser; Katarzyna Rodchenko; Yixuan Zeng; Amy Endrizal (BMC, 2024)
Abstract Background Over 4.53 million arrests were made in 2021 in the United States. People under 26 years of age were more likely to be arrested than older people. Although mental health disparities are prominent in the incarcerated population, the subject has not been closely examined among young adults specifically. Objectives This study examines how criminal justice involvement, specifically arrests, affects the mental health of adults between 18 and 25 years of age. Methods We analyzed secondary data using the 2021 National Survey on Drug Use and Health (NSDUH). The study used a subsample of 13,494 people aged 18 to 25 years, including 7,330 women and 6,164 men. History of arrest was the key independent variable. Depression, serious mental illness (SMI), substance use, suicidal ideation, and suicide attempt were the outcome variables. We performed five multivariate logistic regression models for each outcome variable, controlling for race/ethnicity, income, and education level for men and women separately. Results Of 13,494 respondents, 6.63% had a history of arrest. Among young women, a history of arrest was associated with significantly higher adjusted odds ratios for all mental health concerns. Most notably, a history of arrest increased the likelihood of substance use by a factor of 15.19, suicide attempts by 2.27, SMI by 1.79, suicidal ideation by 1.75, and depression by 1.52. Among young men, a history of arrest was associated with increased adjusted odds ratios (AORs) for substance use (AOR, 13.37; p < .001), suicidal ideation (AOR, 1.45; p = .011), and suicide attempt (AOR, 1.82; p = .044). Conclusions We found a strong relationship between young people having an arrest history and mental health concerns. More specifically, a history of arrest was associated with all mental health concerns among young women, while it was associated with only substance use and suicide among young men. Providing arrestees with appropriate mental health care would benefit them and the criminal justice system by decreasing the odds of recidivism.